Comparative efficacy of oral fexofenadine hydrochloride and intranasal fluticasone furoate in patients with moderate to severe allergic rhinitis: A prospective randomized comparative study. - Dr .Praneeth Kumar K; Dr. N Chetan Rahul; Srilekha, Narendrula; Nihal, Dr . Mohd Abdul (Student's Journal of Health Research Africa, 2025)
Background Allergic rhinitis (AR) is a prevalent chronic condition with a significant impact on quality of life. Pharmacotherapy with non-sedating antihistamines and intranasal corticosteroids remains the mainstay, though comparative evidence in Indian settings is limited. This study aimed to evaluate and compare the clinical efficacy of oral fexofenadine hydrochloride and intranasal fluticasone furoate in patients with moderate to severe AR. Methods A prospective comparative study was conducted on 100 patients aged 16–55 years presenting with moderate to severe AR at a tertiary care centre. Participants were randomized into two equal groups: oral fexofenadine 120 mg once daily (Group OF) and intranasal fluticasone furoate spray, one puff daily (Group NF). Baseline demographic characteristics, symptom scores, and visual analogue scale (VAS) ratings were recorded. Patients were followed up weekly for four weeks. Results Baseline demographic and clinical characteristics were comparable between groups (Table 1). Both groups demonstrated significant reduction in total symptom scores after 4 weeks (p < 0.001), with mean post-treatment scores of 1.16 ± 3.36 in Group OF and 1.90 ± 3.85 in Group NF (Table 2). Severity distribution showed that most patients shifted from severe to moderate categories without intergroup difference (Table 3). However, fluticasone produced greater improvement in nasal obstruction, sneezing, and nasal discharge compared with fexofenadine (Table 4). VAS scores confirmed the superior efficacy of intranasal fluticasone in reducing overall symptom burden (Table 5). Conclusion Both oral fexofenadine and intranasal fluticasone furoate are effective in alleviating symptoms of moderate to severe AR. Fluticasone demonstrated superior improvement in nasal symptoms and VAS reduction, suggesting it may be preferred as first-line therapy. Recommendations For patients with prominent nasal obstruction or persistent AR, intranasal corticosteroids should be prioritized. Antihistamines may be considered when systemic symptoms or patient preference for oral therapy exist.